Why I No Longer Believe Social Media Is Cool . . . (July 2019) - Hurley, Zoe
Web 2.0. seemingly offered empowering opportunities for women globally. While #hashtags gained momentum, liberating women to speak-out against sexual oppression, forging networks for the right to learn to drive, to bridge the gender pay gaps, and to close digital divide, the era of the posthuman, postdigital, and postgender seemed to be just around the corner. A key aspect of this apparent empowerment has been the visual scope of social media that allows women to show the world who they are and how they want to be seen. Teaching in a media and communications program at a university in Dubai, I became interested in the emerging trend of Arab women presenting their lives on social media via image-sharing platforms such as Instagram and Snapchat and assumed that these practices challenged gender inequalities.